Taurine attenuates ischemia-reperfusion injury and prevent magnesium efflux in isolated rat liver - Rahman, Md Mizanur; Kang, Hyung Sub (Annals of Bangladesh Agriculture, 2025)
Ischemia reperfusion injury (IRI) and severe disruption of inorganic ion homeostasis lead to massive cell death. Taurine is a sulfur-containing amino acid that maintains cell homeostasis and functions with ion flux regulating properties. Our hypothesis is that pre- and post-ischemic treatment with taurine reduces ischemia-reperfusion injury and inhibits magnesium (Mg2+) efflux, which promotes tissue survival from oxidative stress. Isolated rat livers were flushed with Krebs-Henseleit buffer (KHB) for 5-10 min followed by Mg2+ free KHB for 10 min and whole organ ischemia was induced by stopping perfusion for 30 min. Livers were treated with taurine (20mmol/L) 5 min before (BT-isc) and after (AT-isc) ischemia. The livers were then reperfused with oxygenated Mg2+ free KHB for 90 min and the necessary effluents were collected for estimation of Mg2+ efflux by AAS. Liver samples were collected and lactate dehydrogenase (LDH) levels and superoxide dismutase (SOD) activity and total and phospho ERK1/2, Bcl and Bax proteins were measured in liver homogenates by specific assays and Western blotting methods. Mg2+ efflux, LDH, SOD, total and phospho ERK1/2, Bax and Bcl increased significantly (p < 0.05) during reperfusion in the non-treated control (NT-isc) livers. Taurine treatment before and after ischemia significantly reduced Mg2+ flux into the effluent. LDH and SOD activity in liver tissue during the reoxygenation period were found to be significantly decreased compared to the untreated group. Taurine treatment significantly decreased total and phospho ERK1/2, Bax and Bcl proteins in perfused livers compared to untreated controls. Comparison between pre- and post-ischemia taurine treatment indicated that taurine pre-treatment provided better protection against reperfusion injury than post-ischemia treatment. Taurine supplementation treatment before and after ischemic liver injury may be beneficial for better recovery of Mg2+ in the isolated liver and may be effective in protecting the transplanted liver from ischemia-reperfusion injury in the recipient. Ann. Bangladesh Agric. 28(1): 181-191